Meta-Analysis of the Effect of Policy Lockdown on Anxiety in Adults - Rohmah, Isna Nur; Sekar, Fauzia Ichlasul; Samudera, Galang Aji; Anasulfalah, Hakim; Ningsih, Hepti Widia; Paramastri, Izdihar Azzah; Wijayanto, Masromi Hendria; Arianty, Meike; Putra, Muhammad Dudayev Caesar; Husein, Muhammad Fajar (Journal of Health Policy and Management, 2021)
Background: On March 11, 2020, the World Health Organization (WHO) has declared an outbreak of a new coronavirus (COVID-19) as a global pandemic. In responding to the threat of the COVID-19 virus pandemic, policymakers have implemented a policy lockdown that can cause psychological distress, one of which is anxiety. This study aims to examine the effect of the policy lockdown on anxiety in adults using a meta-analysis.Subjects and Method: Meta-analysis was performed by searching for articles from the database, namely PubMed, Google Scholar, Science Direct, Scopus, and Crossref. The keywords used are "Anxiety" AND "Adult" AND "COVID-19" OR "SARS-CoV-2" AND "Lockdown" OR "Movement Restriction" OR "quarantine" OR "shutdown". The inclusion criteria in this study were full-text articles with a cross-sectional design, in English, published in the period 2019-2021. Analysis of the article using RevMan 5.3.Results: Four articles were analyzed. The results of the meta-analysis showed that anxiety in adults with the implementation of the policy lockdown was 1.94 times more at risk than those who did not implement the policy lockdown, but it was not significant in increasing anxiety in adults (aOR= 1.94; 95% CI= 0.79 to 4.74; p= 0.150).Conclusion: Anxiety in adults with the implementation of the policy is lockdown more at risk than those who have not implemented the policy lockdown, but it is not significant in increasing anxiety in adults. Keywords: Anxiety, lockdown, covid-19 Correspondence: Isna Nur Rohmah. Health Polytechnic, Ministry of Health, Semarang. Jl. Tirto Agung, Pedalangan, Banyumanik, Semarang City, Central Java 50268. Email: isnanr28@gmail.com. Mobile: +6281327215685Journal of Health Policy and Management (2021), 06(02): 139-147https://doi.org/10.26911/thejhpm.2021.06.02.06